2016
DOI: 10.1021/acscatal.6b00101
|View full text |Cite
|
Sign up to set email alerts
|

N-Doped Food-Grade-Derived 3D Mesoporous Foams as Metal-Free Systems for Catalysis

Abstract: A challenging task of modern and sustainable catalysis is to rethink key processes at the heart of renewable energy technology in light of metal-free catalytic architectures designed and fabricated from cheap and easily accessible building blocks. This contribution describes the synthesis of highly N doped, carbon nanotube (CNT)-netting composites from cheap raw materials. With physical mixtures of CNTs and food-grade components as the starting materials, their thermal treatment generates foamy, N-doped carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 115 publications
3
77
0
Order By: Relevance
“…Upon heating, glucose carbonization happens at 250°C, [30] gases release from NH 4 Cl to blow the carbon skeleton and corrode the skeleton into porous morphology at 350°C. The foam framework is formed by the gas template role of NH 4 Cl under the protection of the as-formed carbon on the matrix. The foam framework is formed by the gas template role of NH 4 Cl under the protection of the as-formed carbon on the matrix.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Upon heating, glucose carbonization happens at 250°C, [30] gases release from NH 4 Cl to blow the carbon skeleton and corrode the skeleton into porous morphology at 350°C. The foam framework is formed by the gas template role of NH 4 Cl under the protection of the as-formed carbon on the matrix. The foam framework is formed by the gas template role of NH 4 Cl under the protection of the as-formed carbon on the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…[1] Various strategies have been adopted to prepare 3D carbon materials, such as self-assemble method, [2] direct-templated chemical vapor deposition (CVD) [3] and carbonization of 3D organic templates [4] , and the fruitful 3D structured carbon matrix has been fabricated (e. g., 3D graphene aerogel, [5] carbon foam [6] and 3D CNTs foam [7] ). [1] Various strategies have been adopted to prepare 3D carbon materials, such as self-assemble method, [2] direct-templated chemical vapor deposition (CVD) [3] and carbonization of 3D organic templates [4] , and the fruitful 3D structured carbon matrix has been fabricated (e. g., 3D graphene aerogel, [5] carbon foam [6] and 3D CNTs foam [7] ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most studied form of these metal-free catalysts consisted of carbon nanotubes doped with nitrogen atoms, which has been extensively used in several catalytic processes [8][9][10][11][12][13]. Recently, work reported by Pham-Huu and Gambastiani [14,15] has shown that nitrogen-doped mesoporous carbon film, synthesized from food stuff raw materials, displays a high performance for different catalytic processes such as oxygen reduction reaction (ORR), direct dehydrogenation of ethylbenzene and selective oxidation of H 2 S. Such nitrogen-doped metal-free catalysts display an extremely high stability as a function of time on stream or cycling tests which could be directly attributed to the complete lack of sintering consecutively to the direct incorporation of the nitrogen atoms inside the carbon matrix.…”
Section: Introductionmentioning
confidence: 99%